Religious Linguistics Code in the Sharenting Content of Muslim Momfluencers on Social Media - Arum Rindu Sekar Kasih; Suhandano Suhandano; Aprillia Firmonasari (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2026)
Sharenting among Muslim momfluencers has emerged as a significant social phenomenon, often blending parenting documentation with Islamic values through religious linguistic codes. This study analyzes the use of terms, phrases, and symbols rooted in Islamic teachings within sharenting content on Instagram. Using a sociolinguistic approach, the research explores how verbal elements construct religious identity while simultaneously engaging a digital audience. Data were collected via digital observation of a Muslim momfluencer’s Instagram content, focusing on the intersection of religious values, motherhood, and daily life. The analysis examines captions containing Quranic verses, hadiths, prayers, and Islamic terminology to identify how these codes are delivered and influenced by socio-cultural contexts. The findings reveal that religious linguistic codes are used strategically to convey Islamic values, establish emotional connections, and enhance the influencer’s religious persona. Beyond mere expression, these codes serve as an effective branding method to attract like-minded Muslim audiences. Complemented by visual cues such as syar'i attire and symbols of worship, sharenting becomes a performative medium for promoting religious narratives and generating social capital. This research provides critical insights into the evolving relationship between language, religion, and parenting in the social media era.